2018
DOI: 10.1007/s10930-018-9785-7
|View full text |Cite
|
Sign up to set email alerts
|

WD40 Repeat Proteins: Signalling Scaffold with Diverse Functions

Abstract: The WD40 domain is one of the most abundant and interacting domains in the eukaryotic genome. In proteins the WD domain folds into a β-propeller structure, providing a platform for the interaction and assembly of several proteins into a signalosome. WD40 repeats containing proteins, in lower eukaryotes, are mainly involved in growth, cell cycle, development and virulence, while in higher organisms, they play an important role in diverse cellular functions like signal transduction, cell cycle control, intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
168
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(182 citation statements)
references
References 143 publications
1
168
0
1
Order By: Relevance
“…The process of septation is of fundamental importance as it gives the fungus the ability to undergo differentiation specifically in conidiation or sporulation and formation or tissue-like structures (Mouriño-Pérez, 2013), which might account for the abnormal sporulation (conidial and blastopore production) and differentiation of hyphal bodies in the insect seen in the mutant due to defect in septum formation to some extent. In addition, some Bbmcm1-mediatedcycle-associated genes, such as protein tyrosine phosphatase (Pyp1), WD40 repeats containing protein and SCF E3 ubiquitin ligase complex Fbox protein grrA-encoding genes, are also involved in sexual development, and/or virulence and disease development in some fungi (Santo et al, 1996;Han et al, 2007;Jain and Pandey, 2018), further suggesting a link between Bbmcm1-mediated cell cycle and fungal growth, cell morphologisis, development and virulence in B. bassiana.…”
Section: Discussionmentioning
confidence: 99%
“…The process of septation is of fundamental importance as it gives the fungus the ability to undergo differentiation specifically in conidiation or sporulation and formation or tissue-like structures (Mouriño-Pérez, 2013), which might account for the abnormal sporulation (conidial and blastopore production) and differentiation of hyphal bodies in the insect seen in the mutant due to defect in septum formation to some extent. In addition, some Bbmcm1-mediatedcycle-associated genes, such as protein tyrosine phosphatase (Pyp1), WD40 repeats containing protein and SCF E3 ubiquitin ligase complex Fbox protein grrA-encoding genes, are also involved in sexual development, and/or virulence and disease development in some fungi (Santo et al, 1996;Han et al, 2007;Jain and Pandey, 2018), further suggesting a link between Bbmcm1-mediated cell cycle and fungal growth, cell morphologisis, development and virulence in B. bassiana.…”
Section: Discussionmentioning
confidence: 99%
“…eIF2A N-terminal part was predicted to adopt a WD-repeat β-propeller fold, the structure of which (for yeast Schizosaccharomyces pombe eIF2A protein) has been solved at 2.5Å resolution [105]. Interestingly, the C-terminally truncated S. pombe eIF2A fragment (residues 1-424) adopts an unconventional 9-bladed β-propeller fold [105] with the same overall topology as many other β-propeller proteins [106,107]. Homology modeling of the human eIF2A (Figure 4) suggests that human eIF2A N-terminal domain (residues 1-415) may also adopt the same 9-bladed β-propeller fold and that the C-terminal domain (residues 416-585) may be less structured and, perhaps, on its own consist of 2-3 smaller subdomains (with very C-terminal fragment residues 533-585 represented by a helix-bundle) (Figure 4).…”
Section: Eif2a Structurementioning
confidence: 99%
“…This study identified an additional 23 domains that formed bigrams with CYP domains. Five of the previously identified domain combinations were ubiquitous to all oomycetes: FKBP (PF00254; oomcCYP03), GRX (PF00462; oomcCYP04), RRM (PF00076; oomcCYP05), WD40 repeat (PF00400; oomcCYP06), and U-box (PF04564; oomcCYP08) domains [26][27][28][29][30]. FKBP-3TPR-CYP bigram has been reported to be present in unicellular eukaryotes, including ciliophora, oomycetes, diatoms, and dinoflagellates, and as inhibiting calcineurin (protein phosphatase 2B) in the presence of the cognate drugs to exhibit family-specific drug sensitivity [31,32].…”
Section: Structure Analysismentioning
confidence: 99%